FREEDOM OF THE INFORMATION SPACE. IS IT A REALITY OR ILLUSION? - Elena V. Korableva (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose: to define and analyze the limits of freedom and personal fulfillment in the information space in accordance with the change of the vector information and technical characteristics of social development. Methodology of scientific cognitive activity allows you to explore new educational requirements, acquisition of new skills, knowledge and new ways of thinking that can provide adequate person entering into a different social environment to change the parameter; identify behavioral change person's standards and values. Scientific novelty reflected in the correlation of real human freedom posed by the technological capabilities of the time, and the imaginary freedom that can undermine the stability of the information society on a number of basic directions of its development. Conclusions: 1) socialization in the new socio-cultural information space involves the formation of a complex system of person's intellectual and emotional development. It demands ability to interact with a lot of information, ability to define a kind of needed information and self-nalysis of information and communication space and behavior. 2) There is a lot of freedom in media space nowadays. People faced with the problem of increasing the amount of information. То fit into information flow human should change the way he thinks: develop skills in algorithmic approach to information processing, structured analytical thinking. It requires a structured analytical thinking. 3) The open architecture of the Internet space allows creating new areas and communities. It expands the boundaries of existing online communities. The new communicative surroundings are radically transforming traditional communication between people. It is destroying channel information, experience and spiritual values created by men. Absolute informational availability creates an illusion of complete human’s independence from social relations and personal communication, isolates people from each other, deprives of a sense of belonging and creates the position of bystander. 4) So called freedom has created new life strategies and undermines the stability of the information society.